2010
DOI: 10.1002/jgm.1470
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term human growth hormone expression and partial phenotypic correction by plasmid‐based gene therapy in an animal model of isolated growth hormone deficiency

Abstract: We report for the first time sustained levels of circulating hGH after intramuscular naked DNA administration and, consequently, a highly significant weight increase of dwarf 'little' mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
20

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 47 publications
1
18
0
20
Order By: Relevance
“…Intramuscular injection of hGH plasmid with electroporation was performed in dwarf mice [86]. Circulating hGH levels were detected up to 60 days after gene transfer, leading to a significant increase of body weight in the mice.…”
Section: Systemic Diseasementioning
confidence: 99%
“…Intramuscular injection of hGH plasmid with electroporation was performed in dwarf mice [86]. Circulating hGH levels were detected up to 60 days after gene transfer, leading to a significant increase of body weight in the mice.…”
Section: Systemic Diseasementioning
confidence: 99%
“…Hydrodynamic transfer has been successfully applied in dogs 23 , but, as pointed out by the authors, other routes for gene transfer can be more convenient for humans. As already mentioned, our group started working with the administration of naked DNA and has described a strategy for in vivo GH gene therapy based on electroporation of hGHcoding plasmid in the quadriceps muscle of lit/lit and lit/scid mice 6 . Muscle was chosen for the establishment of the methodology since it has been demonstrated that gene delivery vectors can be stably maintained in postmitotic fibers after their injection and that this tissue is able to provide a long-term release of the therapeutic protein.…”
Section: Even Though Administration Via Muscle Is S O M E W H a T M Imentioning
confidence: 99%
“…A much better option would appear to be the direct administration of naked plasmid DNA, a methodology that has been successfully adopted by several authors in the last decade. Analysis of growth parameters such as body weight, organ weight (quadriceps muscles, liver, kidneys, heart and spleen) and total (nose-to-tail) length of the animals have been used to study the endocrine and local (autocrine/paracrine) effects of hGH in greater depth after intramuscular DNA administration in immunodeficient dwarf mice (lit/scid) 6 . Although the majority of the strategies described for GH gene therapy are still limited by the absence of an appropriate mechanism for regulating in vivo hormone expression and secretion, a number of factors favor in vivo drug generation as the best alternative.…”
mentioning
confidence: 99%
“…Derivam dos plasmídeos comerciais pcDNA 3.1(+) e pcDNA 3.1(-), da Invitrogen (Carlsbad, CA, EUA), os quais foram modificados com a inserção da sequência genômica (gDNA) ou complementar (cDNA) do gene do hGH (Oliveira, 2010 A seguir, o músculo foi eletroporado, seguindo as condições estabelecidas para combinação de pulsos de alta e baixa voltagem (Hojman e col., 2011) para os camundongos normais, com 1 pulso de 800 V/cm e 1 pulso de 100 V/cm, com duração de 400 milisegundos e um intervalo de 1 segundo entre o pulso alto e o baixo. Os animais da linhagem lit/lit receberam 8 pulsos de 150 V/cm, com duração de 20 milisegundos e intervalo de 0,5 segundos entre os pulsos (Oliveira e col., 2010).…”
Section: Plasmídeosunclassified